Self-assembled mPEG–PCL-g–PEI micelles for simultaneous codelivery of chemotherapeutic drugs and DNA: synthesis and characterization in vitro - Shi S (Dove Medical Press, 2012)
Shuai Shi, Xuechen Zhu, QingFa Guo, Yingjing Wang, Tao Zuo, Feng Luo, Zhiyong QianState Key Laboratory of Biotherapy and Cancer Center, West China Hospital, West China Medical School, Sichuan University, Chengdu, People's Republic of ChinaBackground: In this paper, a series of amphiphilic triblock copolymers based on polyethylene glycol–poly ε-caprolactone–polyethylenimine (mPEG–PCL-g–PEI) were successfully synthesized, and their application for codelivery of chemotherapeutic drugs and DNA simultaneously was investigated.Methods and results: These copolymers could self-assemble into micelles with positive charges. The size and zeta potential of the micelles was measured, and the results indicate that temperature had a large effect on the micelles obtained. In vitro gene transfection evaluation in cancer cells indicated that the self-assembled micelles could serve as potential gene delivery vectors. In addition, hydrophobic drug entrapment efficiency and codelivery with the gene was also studied in vitro. The self-assembled micelles could load doxorubicin efficiently and increase cellular uptake in vitro, while maintaining high gene transfection efficiency.Conclusion: The triblock copolymer mPEG–PCL-g–PEI could be a novel vector for codelivery of drug and gene therapy.Keywords: self-assembly, triblock copolymer, DNA, drug codelivery, gene transfection